Developing Entrepreneurship through Training Intervention : An Empirical Investigation towards Effectiveness - Dutta, Gautam; Borbora, Saundarjya (Gyan Management Journal, 2007)
This paper di cuss · about the effectiveness of entrepreneur hip developm nt training in term of germination of enterprise . ccording to the post training status of the trainees they are das ified as "doers" "dreamer ", and "duds". The ’ do r are tho e who could launch their enterprise after training; the ’ dreamer ’ are in the proce s of etting up their enterprises and the "duds" abandoned the jdea of becoming entrepreneur . A survey of 2616 respondents, who participated in entrepreneurship development trainingorganized in northeastern region of India during April, 1990- March! 996, reveal that 21.75 percent became "doers" 20.68 percent "dreamer " and 57 .87 percent "duds". Analysi of "doer " reveals that majority of them are only mod rately educated, age wj e in their late thirties, married and were unemployed before starting enterp1ises. Stepwise multiple regression analysi of the causes of delay in launching enterpri es by the dreamer reveal that delay in enterprise launching have been influenced to the extent of 68.1 percent by two factors namely ’lack of startup finance’ and ’ lack of family